Investigation of a Lomentospora prolificans case cluster with whole genome sequencing - Peter Boan; Stanley Pang; Dianne J. Gardam; Helen Darragh; Matthew Wright; Geoffrey W. Coombs (Medical Mycology Case Reports, 2020)
Lomentospora prolificans has caused outbreaks in immunocompromised patients. We performed whole genome sequencing (WGS) on 4 L. prolificans isolates from infections occurring during an 8-month period in the haematology unit at Hospital 1., and 2 isolates from unrelated infections at Hospital 2., showing a high number of mutational differences (>10,000 single nucleotide polymorphisms) between L. prolificans isolates from Hospital 1. Novel typing of isolates by WGS did not demonstrate a single causative strain.